Canadian Indigenous Cognitive Assessment (CICA): Inter‐rater reliability and criterion validity in Anishinaabe communities on Manitoulin Island, Canada. Issue 1 (9th June 2021) - Walker, Jennifer D.; O'Connell, Megan E.; Pitawanakwat, Karen; Blind, Melissa; Warry, Wayne; Lemieux, Andrine; Patterson, Christopher; Allaby, Cheryl; Valvasori, Meghan; Zhao, Yantao; Jacklin, Kristen
Abstract: Introduction: Despite increasing dementia rates, few culturally informed cognitive assessment tools exist for Indigenous populations. The Canadian Indigenous Cognitive Assessment (CICA) was adapted with First Nations on Manitoulin Island, Canada, and provides a brief, multi‐domain cognitive assessment in English and Anishinaabemowin. Methods: Using community‐based participatory research (CBPR) methods, we assessed the CICA for inter‐rater and test–retest reliability in 15 individuals. We subsequently evaluated validity and established meaningful CICA cut‐off scores in 55 individuals assessed by a geriatrician. Results: The CICA demonstrated strong reliability (intra‐class coefficient = 0.95 [0.85, 0.98]). The area under the curve (AUC) was 0.98 (0.94, 1.00), and the ideal cut‐point to identify likely cases of dementia was a score of less than or equal to 34 with sensitivity of 100% and specificity of 85%. Discussion: When used with older First Nations men and women living in First Nations communities, the CICA offers a culturally safe, reliable, and valid assessment to support dementia case‐finding.